Omics analysis of the effect of cold normal saline stress through gastric gavage on LPS induced mice - Li, Jing; Cui, Zhihao; Wei, Ming; Almutairi, Mikhlid H.; Yan, Peishi (Frontiers in Microbiology, 2023)
Cold stress is a significant environmental stimulus that negatively affects the health, production, and welfare of animals and birds. However, the specific effects of cold stimulation combined with lipopolysaccharide (LPS) on the mouse intestine remain poorly understood. Therefore, we designed this research to explore the effect of cold stimulation + LPS on mice intestine via microbiome and microbiota sequencing. Forty-eight mice were randomly divided into four experimental groups (n = 12): Control (CC), LPS-induced (CL), cold normal saline-induced (MC) and LPS + cold normal saline-induced (ML). Our results showed body weight was similar among different groups of mice. However, the body weight of mice in groups CC and CL were slightly higher compared to those in groups MC and ML. The results of gene expressions reflected that CL and ML exposure caused gut injury and barrier dysfunction, as evident by decreased ZO-1, OCCLUDIN (P < 0.01), and CASPASE-1 (P < 0.01) expression in the intestine of mice. Moreover, we found that cold stress induced oxidative stress in LPS-challenged mice by increasing malondialdehyde (MDA) accumulation and decreasing the antioxidant capacity [glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), total and antioxidant capacity (T-AOC)]. The cold stress promoted inflammatory response by increased IL-1β in mice treated with cold normal saline + LPS. Whereas, microbiome sequencing revealed differential abundance in four phyla and 24 genera among the mouse groups. Metabolism analysis demonstrated the presence of 4,320 metabolites in mice, with 43 up-regulated and 19 down-regulated in CC vs. MC animals, as well as 1,046 up-regulated and 428 down-regulated in ML vs. CL animals. It is Concluded that cold stress enhances intestinal damage by disrupting the balance of gut microbiota and metabolites, while our findings contribute in improving management practices of livestock in during cold seasons.